"Maribor je prihodnost!" - Kordiš, Meta (Etnolog. Nova vrsta (Ljubljana), 2020)
In addition to the instrumentalisation of culture with the aim of forging European connections, the main goal of the ECC mega-project is to encourage the tertiary sector as well as urban renovation and revitalisation of cities. In spite of all the promises and grand plans, there remains the impression that the Maribor 2012 project left nothing behind. But nonetheless, since 2012 a number of lively venues for grassrots cultural production have sprung up. A range of horizontal connections among different people and groups has encouraged lively cultural and social activities, which are in turn encouraging reflection on where and how to continue, i.e. what sort of a city they want to help create.
Keywords: Evropska prestolnica kulture; kulturna produkcija; Maribor; nevladni kulturni sektor